Cultural Repercussion on Mediation: Exploring A Culturally Resonant Mediation Approach Germane to Asia - Chowdhury, Jamila A. (Journal of Malaysian and Comparative Law, 2015)
Cultures always have profound impacts on what people do, and more importantly how they do it. The practice of mediation is not an exception. Therefore, a dynamic mediator also endeavours to mitigate ‘cultural conflict’ in a dispute so that cultural departure does not exacerbate or create another conflict. Adapting Hofstede’s theory on ‘style of dispute resolution practices in Asian commercial organizations’ into mediation, this paper explains why a bit of an evaluative approach from mediators would be more appreciated and fruitful in Asian cultural context. Practices of mediation in indigenous Asian societies are also analyzed to deduce that historically Asian people are accustomed with practicing evaluative mediation to resolve their disputes. In brief, theories and practices of mediation synthesized in this paper would assist puzzled practitioners and policy makers in Asia to choose between evaluative and facilitative mediation. This paper, however, forms a strong argument why practice of evaluative mediation would be more productive and apposite in Asian context.